EVALUASI INDEKS KINERJA SISTEM TANAMAN ANGGREK HITAM HIDROPONIK DFT BERBASIS RUMAH TANAMAN MENGGUNAKAN AHP - Prawiranegara, Boy Macklin Pareira; Sugandi, Wahyu Kristian; Meilani, Diah; Situmorang, Yogina Lestari Ayu (Department of Agroindustrial Technology, Bogor Agricultural University, 2024)
This research employed the Analytical Hierarchy Process (AHP) method to evaluate the performance of the black orchid hydroponic system using Deep Flow Technique (DFT) based on Plant House during the acclimatization phase. The objective of this study was to assess the system's performance considering parameters such as plant height, energy, water requirements, energy costs, nutrient needs, and ease of maintenance. The research methodology combines qualitative and quantitative approaches involving 50 respondents from various orchid communities in several cities in Indonesia. The data were analyzed using AHP to determine the priority weights for the tested alternatives. The results show that plant height holds the highest weight with 0.4394. Comparing the DFT black orchid system with the conventional one reveals differences in performance parameters like energy, water requirements, energy costs, nutrient needs, plant height, and ease of maintenance. The DFT hydroponic system outperforms the conventional system with a total performance index of 0.8832, interpreted as